“Neither a cent for macumbeiro”: about moral control over public budget under bolsonarism: about moral control over public budget under bolsonarism (Simbiótica. Revista Eletrônica, 2024)
Discussing a statement made by the former president of the Fundação Cultural Palmares, the article covers the characteristics of “Bolsonarism” and its relations with certain political groups and social movements. Taking use of economic sociology, it is proposed that the foundations that support relational hostility and cultural disrespect against these groups are transposed into processes which involves the transfer of resources, goods and services from the public budget. It concludes that there are ideas, in some cases translated into practical actions, that allow us to speak of a discriminatory and moral interest in the distribution of public resources, in flagrant non-compliance with legal diplomas and endangering the advances made by the Brazilian State with regard to the Policies for the Promotion of Racial Equality.
Keywords: economic sociology; racial equality; public budget; bolsonarism